Engineered M2a macrophages for the treatment of osteoarthritis - Liang, Chi; Wu, Song; Xia, Guang; Huang, Junjie; Wen, Zi; Zhang, Wenxiu; Cao, Xu (Frontiers in Immunology, 2022)
Background: As a central regulator of innate immunity, inflammation, and tissue homeostasis, macrophage has great potential as an ideal seed cell for disease-modifying cell therapy for osteoarthritis (OA). However, this has not yet been studied. In this study, we used genome editing to lock macrophages with anti-inflammatory and pro-regenerative M2a polarity in vitro. We aimed to explore the effects of intra-articular transplantation of this locked M2a (L-M2a) macrophages on OA. Methods: Macrophages were isolated from the bone marrow of rats. L-M2a macrophages were constructed by simultaneous TNFR1 knockout and IL-4 overexpression, using Cas9-ribonuclear proteins (Cas9-RNP) and electroporation. In vitro, L-M2a macrophages were treated with OA synovial fluid or co-cultured with OA chondrocytes or fibroblast-like synoviocytes (FLS). In vivo, L-M2a macrophages were injected intra-articularly to evaluate their homing and engrafting abilities and therapeutic effects on OA progression using a rat model. Results: L-M2a macrophages displayed a typical anti-inflammatory phenotype similar to that of M2 macrophages in vitro. In OA microenvironment, L-M2a macrophages maintained a stable anti-inflammatory phenotype, whereas unmodified M2 macrophages lost their phenotype and switched to M1 polarity. L-M2a macrophages demonstrated a potent anti-inflammatory effect in crosstalk with OA-FLSs and an anti-degenerative effect in crosstalk with OA chondrocytes. In vivo, compared with M2 macrophages and exosomes, L-M2a macrophages exhibited significantly superior therapeutic effects in OA by successfully resolving inflammation, restoring tissue homeostasis, and promoting cartilage regeneration. Conclusion: The engineered L-M2a macrophages maintained a superior anti-inflammatory and pro-regenerative capacity in the inflammatory OA microenvironment and represents an ideal new strategy for the disease-modifying therapy of OA.